Strategi Komunikasi Program Dapur Sehat Atasi Stunting Oleh BKKBN Jawa Tengah Sebagai Upaya Penurunan Angka Stunting di Kota Semarang - Sutanto, Hosea Richard; Arifin, Pupung (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Dapur Sehat Atasi Stunting (Healthy Kitchen Overcomes Stunting) or DAHSAT is one intervention step that was launched by BKKBN to tackle the problem of stunting. This study aimed to elucidate the communication strategy of BKKBN Jawa Tengah when implementing DAHSAT in Semarang. The Communication Strategy will be further examined in the stages of planning, implementation, and evaluation. This research was conducted using the case study method through in-depth interview techniques. BKKBN has not been optimal in developing the communication strategy of the DAHSAT Program, especially at the stage of mapping the sociodemographic aspects of the target audience. The research result indicates that BKKBN Jawa Tengah had not fully implemented a structured communication strategy. Even though it is not optimal, the health communication process that occurs in the implementation of DAHSAT has helped some communities understand what stunting is and how to prevent it.